Challenges of Chinese EFL Lecturers Attending Online Professional Development in Ningxia: Barriers and Solutions - Kong, Ling-di; Saidon, Mohd Kasri; Saidin, Khaliza (Academic Research Publishing Group, 2017)
Rapid development of information technology provides a favorable and high-quality platform for teachers’ online professional development. However, due to some factors, some teachers are unable to attend their OPD courses successful and effectively.Therefore, the research objective of this study was to assess the challenges of Chinese EFL lecturers attending online professional development (OPD).The participants consist of 100 EFL lecturers from 3 universities in Ningxia.The instrument for data collection used for the study was 20-item questionnaire.The researchers adopted the Cronbach Alpha method to determine the reliability of the instrument.A reliability index of 0.81 was obtained.Two research questions were structured and data collected were analyzed using mean and standard deviation.Findings revealed that, over workload and shortage of time are among the barriers of OPD for EFL lecturers.It was also recommended that less workload and adequate technical support would improve lecturers’ professional development in universities.